2007
DOI: 10.1089/ars.2006.1522
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Upregulation of Parkin in Response to ER Stress

Abstract: Parkin is the gene responsible for a familial form of Parkinson's disease (PD) termed autosomal recessive juvenile parkinsonism (AR-JP)/PARK2. Parkin has been shown to protect cells from endoplasmic reticulum (ER) stress and oxidative stress, presumably due to its ubiquitin ligase (E3) activity that targets proteins for proteasomal degradation. Although the authors showed that parkin is upregulated in response to ER stress, subsequent reports suggest that it does not represent a universal unfolded protein resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…39 It was found that PARK2 is more prone to be upregulated by ER stress in neurons compared with other cell types. 44 Although the cell specific mechanisms were not fully elucidated, our data at least suggest that ER stress conferred brain protection in our model, may be largely due to its direct actions on neurons. In addition, we interestingly found that both Atf4 and Eif2s1 silencing reduced PARK2 expression in intact neurons in a dose-and time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…39 It was found that PARK2 is more prone to be upregulated by ER stress in neurons compared with other cell types. 44 Although the cell specific mechanisms were not fully elucidated, our data at least suggest that ER stress conferred brain protection in our model, may be largely due to its direct actions on neurons. In addition, we interestingly found that both Atf4 and Eif2s1 silencing reduced PARK2 expression in intact neurons in a dose-and time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies do suggest a link between Parkin function and ER stress. Parkin expression is increased in response to ER stress (Wang et al, 2007), and accumulation of the Parkin substrate Pael-R leads to ER stress (Imai et al, 2001; Kitao et al, 2007). Further, findings by Yamamoto et al suggest that ER stress results in a decrease in the phosphorylation rate of Parkin concordant with an increase in ubiquitin ligase activity (Yamamoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, no or only a few positive control images are shown in most articles, hindering the comparative literature survey. Also, SH-SY5Y cells are known to respond inconsistently to the same differentiation treatment, depending on their cell source [49] or possibly passage number. Therefore, the variation reported may be at least in part due to the origin of the cells and different aspects regarding their handling, highlighting the importance of the proper reporting of all protocols involved.…”
Section: Main Textmentioning
confidence: 99%